2019
DOI: 10.1108/cdi-04-2018-0102
|View full text |Cite
|
Sign up to set email alerts
|

Job insecurity and performance over time: the critical role of job insecurity duration

Abstract: Purpose Research on the relationship between job insecurity and job performance has thus far yielded inconclusive results. The purpose of this paper is to offer a more dynamic perspective on the effects of job insecurity on job performance. Design/methodology/approach Drawing from cognitive appraisal theory, research on critical life events, and stress reactions as well as more general theorizing around the role of time, this paper proposes that individuals’ job performance reactions to job insecurity will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 47 publications
1
25
0
1
Order By: Relevance
“…The recent pandemic has severely strained various occupational sectors, many companies have experienced downsizing, many more have closed, and unemployment has risen dramatically ( Rudolph et al, 2020 ). These dynamics raise crucial questions about the impact of such insecurity on job performance, given past ambiguous findings on the topic that have not helped untangle this issue ( Debus et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent pandemic has severely strained various occupational sectors, many companies have experienced downsizing, many more have closed, and unemployment has risen dramatically ( Rudolph et al, 2020 ). These dynamics raise crucial questions about the impact of such insecurity on job performance, given past ambiguous findings on the topic that have not helped untangle this issue ( Debus et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analytic evidence reported the negative impact of job insecurity on task performance (Sverke et al, 2002;Cheng and Chan, 2008;Gilboa et al, 2008). However, while many previous studies have concluded that job insecurity has a negative effect on task performance explicitly, some mixed empirical findings can be found (e.g., Lee et al, 2018;Debus et al, 2019;Pilipiec, 2020;Shin and Hur, 2020). The inconsistency of these findings suggests the need for a closer look at this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The 21st century organisation, both in the public and private sector, continues to be buffeted by multiple factors demanding transformation and change (Barley et al, 2017;Debus et al, 2019). These transforming factors impact on all aspects of organisational operations, including careers (Debus et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The 21st century organisation, both in the public and private sector, continues to be buffeted by multiple factors demanding transformation and change (Barley et al, 2017;Debus et al, 2019). These transforming factors impact on all aspects of organisational operations, including careers (Debus et al, 2019). Before the turn of the 21st century, career scholars were arguing that organisational careers had changed from the traditional model of long-term tenure, linear career progression and organisational career management for the benefit of the organisation (Baruch and Rousseau, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Extent of job insecurity has great impact on job performance (Debus, 2020). FOMO is a known word in media studies, but it affects not only investment decisions (Shiva et al, 2020) but career FOMO affects job choices to a greater extent.…”
Section: Introductionmentioning
confidence: 99%